2018
DOI: 10.1007/978-3-030-00178-0_5
|View full text |Cite
|
Sign up to set email alerts
|

From Words to Images Through Legal Visualization

Abstract: One of the common characteristics of legal documents is the absolute preponderance of text and their specific domain language, whose complexity can result in impenetrability for those that have no legal expertise. In some experiments, visual communication has been introduced in legal documents to make their meaning clearer and more intelligible, whilst visualizations have also been automatically generated from semantically-enriched legal data. As part of an ongoing research that aims to create user-friendly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[11,12,13,14,15,16] The problem is often traced back to the fact that ToS and PP are contracts, and contracts are typically written by lawyers and for lawyers, even though they regulate the mutual interest and relations of lawyers' clients. [17,18,19] In a comprehensive analysis of privacy-related empirical research, Acquisti and colleagues [14] have identified three recurring themes. First, users are uncertain about what privacy trade-offs entail.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12,13,14,15,16] The problem is often traced back to the fact that ToS and PP are contracts, and contracts are typically written by lawyers and for lawyers, even though they regulate the mutual interest and relations of lawyers' clients. [17,18,19] In a comprehensive analysis of privacy-related empirical research, Acquisti and colleagues [14] have identified three recurring themes. First, users are uncertain about what privacy trade-offs entail.…”
Section: Related Workmentioning
confidence: 99%
“…The authors have included some of their own to the list. Moreover, interdisciplinary work taking HCI and legal factors into consideration, address the use of contract visualizations and icons [18,19] to simplify the legalese and the complexity of concepts and terms in ToS and PP statements. We should finally note that machine learning and AI techniques have also been explored to face the challenges of usable GDPR compliance.…”
Section: Related Workmentioning
confidence: 99%